1989
DOI: 10.2337/diab.38.7.932
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-Dependent Low Thymic Hormone Level in Type I Diabetes

Abstract: Zinc is required for optimal functioning of the immune system. It was recently reported that one of the best-known thymic hormones responsible for the maturation and differentiation of the thymus-derived T-lymphocyte line, i.e., serum thymic factor (STF), is biologically active only when bound to zinc ions; in this form it has been called thymulin (Zn-STF). Because low serum and tissue zinc values have been reported to occur in diabetic conditions, and because defects of T-lymphocyte-dependent functions are al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In type 2 diabetes, a single nucleotide polymorphism in SLC30A8, rs13266634 (Arg325Trp), has been reported. The ZnT8 transporter is located on dense core vesicles (DCVs) in β cells and loads the zinc cation into these secretory compartments where it then binds with and stabilizes the hexameric form of insulin [89]. It appears that functional ZnT8 facilitates autocrine and paracrine roles for the zinc ion bursts produced by β cells upon glucose stimulation [86].…”
Section: Deficiency Of Zinc In Diabetes Mellitusmentioning
confidence: 99%
See 2 more Smart Citations
“…In type 2 diabetes, a single nucleotide polymorphism in SLC30A8, rs13266634 (Arg325Trp), has been reported. The ZnT8 transporter is located on dense core vesicles (DCVs) in β cells and loads the zinc cation into these secretory compartments where it then binds with and stabilizes the hexameric form of insulin [89]. It appears that functional ZnT8 facilitates autocrine and paracrine roles for the zinc ion bursts produced by β cells upon glucose stimulation [86].…”
Section: Deficiency Of Zinc In Diabetes Mellitusmentioning
confidence: 99%
“…After secretion, the hexameric structure of insulin dissociates into the active monomer and zinc ions, which is most likely caused by a combination of a rapid decrease in Zn 2+ pressure. Moreover, an in vitro study suggested that the Zn ions co-secreted with insulin during hyperglycemia might contribute to β cell death via a paracrine mechanism [89]. It has been hypothesized that such activity could link hyperinsulinism with β cell necrosis and the ensuing type 2 diabetes.…”
Section: Deficiency Of Zinc In Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficiency of trace elements is commonly seen in malnourished infants and this is closely associated with thymic hypofunction which invariably contributes to low WBC (Mocchegiani et al . ; Rink & Gabriel ).…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect of Zn supplementation in these studies supports the concept that in some populations, suboptimal Zn nutrition is a risk factor for adverse pregnancy outcome. Furthermore, toxicant exposures as well as acute and chronic disease states can reduce the availability of maternal Zn to the embryo (Mocchegiani et al, 1989; Taubeneck et al, 1994). It is important to note that many nutritional studies related to reproduction consider nutrition only after pregnancy has been recognized.…”
Section: Introductionmentioning
confidence: 99%